The impact of nutritional status and appetite on the hospital length of stay and postoperative complications in elderly patients with severe aortic stenosis before aortic valve replacement - Jagielak, Dariusz; Wernio, Edyta; Kozaryn, Radosław; Bramlage, Peter; Gruchała-Niedoszytko, Marta; Rogowski, Jan; Małgorzewicz, Sylwia (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : Severe aortic stenosis (AS) is associated with the reduction of physical activity and muscle mass and may be associated with decreased appetite. Aim : To assess the nutritional status and the impact of nutritional status and appetite on the hospital length of stay and postoperative complications in elderly patients with severe AS before aortic valve replacement. Material and methods : Ninety-nine patients (55 male, 44 female; 74.3 ±5.2 years old) with severe AS and an indication for aortic valve replacement (AVR) were included. The nutritional status was assessed by different questionnaires (7-point Subjective Global Assessment Score – 7-SGA, full-Mini Nutritional Assessment – full-MNA) and anthropometric measurements (body mass index (BMI) kg/m 2 ). Body composition was estimated using multi-frequency bioelectrical impedance analysis. Appetite was assessed by the Simplified Nutrition Assessment Questionnaire (SNAQ). Results : The average BMI of patients was 28.8 ±5.8 kg/m 2 . Results of the 7-SGA and f-MNA questionnaires revealed that 39 patients (39.4%) were at risk of malnutrition. The mean SNAQ score was 15.8 ±1.8. The average length of hospital stay was 10 ±5.8 days. There was a positive correlation of LOS with age (r = 0.26, p = 0.03) and a negative correlation with fat mass (kg) (r = –0.28, p = 0.04) and BMI (r = –0.22, p = 0.03). Postoperative complications were observed in 37 patients (37.4%). Patients who developed complications were older and had poorer nutritional status according to the results of the 7-SGA. Conclusions : Despite many patients undergoing AVR being overweight and obese, a considerable proportion displayed clinical signs of malnutrition. The results suggest that an assessment of nutritional status and appetite in this group of patients should be conducted regularly and that the 7-SGA scale could represent a reliable tool to assess malnutrition.